1988
DOI: 10.1139/b88-178
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution of carbofuran and dimethoate in flowers and their secretion in nectar as related to nectary vascular supply

Abstract: The distribution of two systemic insecticides (carbofuran, dimethoate) in floral parts and nectar of Ajuga reptans L. (Lamiaceae), Brassica napus L. (Brassicaceae), and Vicia faba L. (Leguminosae), which differ in their types of nectary vascular supply, was determined. Radioactivity was detected in all floral organs when excised flowering plant tops were cultured in sucrose solution containing a combination of 14C-labelled and formulated (unlabelled) insecticide. In A. reptans and B. napus, combined nectary ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The latter is most likely with systemic insecticides. Tests with dimethoate and carbofuran suggest that these chemicals are selectively transported into the nectar where they can reach high concentrations (17). Given the large volume of nectar consumed by bumblebees, this could prove to be the most important route of exposure.…”
Section: Pesticidesmentioning
confidence: 99%
“…The latter is most likely with systemic insecticides. Tests with dimethoate and carbofuran suggest that these chemicals are selectively transported into the nectar where they can reach high concentrations (17). Given the large volume of nectar consumed by bumblebees, this could prove to be the most important route of exposure.…”
Section: Pesticidesmentioning
confidence: 99%
“…Systemic pesticides are most likely to occur in nectar and pollen and in nectar their concentrations depends on both the amount and method of secretion. A number of studies have shown contamination of nectar following pesticide exposure (Davis and Shuel, 1988). Investigations with dimethoate and carbofuran in bugleweed (Ajuga reptans), oilseed rape (Brassica napus) and field beans (Vicia faba) showed an apparent selective transport of the insecticides into the nectar as the concentration in nectar often exceeded that in the solution in which the excised flowers were exposed, i.e.…”
Section: Secretion Of Pesticides Into Nectar and Pollenmentioning
confidence: 99%
“…Investigations with dimethoate and carbofuran in bugleweed (Ajuga reptans), oilseed rape (Brassica napus) and field beans (Vicia faba) showed an apparent selective transport of the insecticides into the nectar as the concentration in nectar often exceeded that in the solution in which the excised flowers were exposed, i.e. it is more than passive movement with water (Davis and Shuel, 1988). There are several reports that it is not only the truly systemic pesticides which can be detected in nectar but also penetrating chemicals such as parathion can result in toxic nectar for up to 24 hours (Jaycox, 1964).…”
Section: Secretion Of Pesticides Into Nectar and Pollenmentioning
confidence: 99%
“…Almost all tests conducted so far have been on B. terrestris, and suggest that toxicity is similar to that found in honeybees. Tests with dimethoate and carbofuran suggest that these chemicals are selectively transported into the nectar where they can reach high concentrations [13]. When colonies are large it is likely that they can tolerate the loss of some of their workers.…”
Section: Effect Of Insecticidesmentioning
confidence: 99%